Analisis Quantity Take-Off Menggunakan BIM Pada Proyek Jalan Tol “X” - Travis, Karina; Martina, Nunung; Safri (Journal of Applied Civil Engineering and Infrastructure Technology, 2021)
In large and complex construction projects, Building Information Modelling (BIM) is important in the globalization of construction technology. Through the implementation of BIM, it is hoped that the “X” Toll Road Project can minimize errors. The problems that occurs in the field is that the QTO calculation using AutoCAD with Microsoft Excel tools in the initial estimate is less accurate so that it results in a miss calculation in the implementation, BIM is expected to be a solution to this problem. A case study was conducted to compare the quantity take-off in toll road construction on Overpass Interchange “X” and Access Roads using BIM and conventional. Data analysis was obtained from carrying out quantity take-off work using BIM and Conventional CAD as well as conducting interviews with BIM experts. Based on the research conducted, there are differences in the calculation of the take-off quantity between BIM and conventional, the percentage difference in the calculation obtained is the difference in earthworks ±4,375%, structural excavation difference ± 1,7%, pavement difference ± 4.4%, structural concrete difference ± 0.1%, and other work 0% difference. BIM can streamline more actual volume, but it takes a long time for beginners to get accurate. BIM is influenced by the level of modeling detail, if the modeling is not modeled properly, it will give wrong volume calculation results. Compared to conventional methods, using BIM at the beginning of planning is very effective in preventing re-design as well as inefficient designs and miss calculations.